THE EFFECT OF THE COVID-19 PANDEMIC ON BUDGET MANAGEMENT IN SEPE'E VILLAGE, BARRU DISTRICT, BARRU REGENCY. - Lukman, Sri Hardianti; Pratiwi, Dian; sukmawati (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal